Rubberized Glutardialdehyde modiﬁed starch plasticized with Ethylene Glycol - Amirul Fauzan Amerudin (2018)
In the current past few decades, self-awareness towards the usage of biodegradable material in our daily life is still low among us. The dependence of the people towards the petroleum-based plastic are rapidly rises in the urbanization of industrial, agriculture, domestic, pharmaceutical activities and others. Thermoplastic starch is biodegradable material to be arising up recently due to its attribute as environment friendly and promote sustainable development. However, there are several weaknesses such as low resistant to water. This may lead to reduce the interest of peoples to use this material. Therefore, this study is conducted in order to overcome this problem respectively. In this study, corn starch is used as the raw material to make the modiﬁed starch. In addition, ethylene glycol is been selected as the plasticizer and the glutardialdehyde is act as the cross-linkage agent whereas natural rubber is added in order to make the modiﬁed starch to become water repellent. The rubber content 0%,20% and 50% is acted as the parameter for this study. Each test is prepared into three samples to get the average reading. Based on the overall result, the physical characteristic shows higher rubber content will has the high retention of water. For the mechanical characteristic, when the rubber content is higher, the tensile strength is lower which make the sample become ﬂexible. Then, when the rubber content increased, the bending strength is also increased. Signiﬁcant of this study is to be easily recycled means that mankind will become more responsible to steward our natural resources while the fact that manufacturing waste can be reused compared to petroleum-foam based.